Marcadores culturais na tradução de Gabriela, cravo e canela para a língua espanhola - Silva, Dayane de Cássia Ferreira da Cruz (2021)
This dissertation aims to carry out a study about the Cultural Markers, from the parallel corpus of the novel Gabriela, cravo e canela (2006 [1958]) by Jorge Amado, in Portuguese and its translation into Spanish, Gabriela, clavo y canela (2007), using the Afro-Brazilian lexicon in the domain of material culture of gastronomy. The analyzed cultural markers were collated with the aid of the WordSmith Tools 7.0 software. The research has an interdisciplinary character, which involves the study of Lexicon, Translation, Linguistics Corpus and Literature. To carry out this dissertation, we used the concepts of lexicon and its areas of study (BARBOSA, 1990; 1995; BIDERMAN, 1998; ISQUERDO, 1996; 1998; 2006; 2007; OLIVEIRA, 1998; 1999; 2000; WELKER, 2004); Linguistics Corpus (BERBER SARDINHA, 2004; 2009; 2012; OTHERO, 2006); the Modalities of Translation (AUBERT, 1998; 2006; ZAVAGLIA, 2006); the Cultural Markers (AUBERT, 2003; 2006; REICHMAN; ZAVAGLIA, 2014); and the Cultural Domains (NIDA, 1945; AUBERT, 1981; 2006); the computational tool WordSmith Tools 7.0 (BERBER SARDINHA, 2004; 2009; 2012), the Lexicographical File (NASCIMENTO; BARREIROS, P., 2018) and Flex (BARREIROS, L., 2017). The cultural markers presented in this dissertation show the vocabulary richness and regional linguistic characteristics brought about in the Amadean novel. In the analysis of the translation performed by the translators, the loan translation modality and the foreign translation strategy were chosen. Based on the analysis and results obtained, it is hoped that this dissertation can contribute to future research in the areas of lexical studies, translation and the Afro-Brazilian lexicon.